Características clínico-epidemiológicas de las malformaciones congénitas músculo-esqueléticas. Hospital Regional Docente de Trujillo. - Castro Sánchez, Diego Raúl (2019)
Objective: Describe the clinical-epidemiological characteristics in live newborns and children treated at the Hospital Regional Docente de Trujillo (HRDT). Material and Methods: Observational, descriptive and retrospective study. 155 medical records of patients with congenital musculoskeletal malformations were reviewed. Results: The prevalence: 2.38 per 1000 live newborns. 63.2% are girls. 63% diagnosed at birth. 48.4% come from Trujillo. Gastroschisis was found in 42% and congenital dislocation of the hip in 25.8%. 57.7% had a birth weight between 2500-4000 gr. The mortality rate: 0.6 per 1000 live newborns. Conclusion: The prevalence: 2.38 per 1000 live newborns. Mortality rate: 0.6 per 1000 live newborns. 63.2% are girls. Gastroschisis and congenital dislocation of the hip were more frequent. 57.7% have a normal birth weight.